Novel radiation sources using relativistic electrons (World Scientific, 1998)
10 chapters: Introduction; radiation by Relativistic Electrons; synchrotron Radiation, undulators, Free - elactron lasers; compton scattering of laser light; coherent bremsstrahlung; channeling radiation;...